Policy uncertainty and aggregate fluctuations - Haroon Mumtaz; Paolo Surico (Queen Mary University of London, School of Economics and Finance, 2013)
This paper estimates the impact on the US economy of four types of uncertainty about (i) government spending, (ii) tax changes, (iii) public debt sustainability and (iv) monetary policy. Following a one standard deviation shock, uncertainty about debt sustainability has the largest and most significant impact on real activity, with negative effects on output, consumption and investment after two years around 0.5%, 0.3% and 1.5% respectively. Uncertainty on the other economic policies has also detrimental consequences but these tend to be smaller and short-lived, especially for taxes and monetary policy. About 30% of output fluctuations are explained by policy uncertainty at most frequencies, with the lion's share accounted for by debt sustainability. Our results are based on a new empirical framework that allows the volatility of identified shocks to have a direct impact on the endogenous variables of an otherwise standard structural VAR.
Keywords: D80; E32; E63; 330; Economic policy uncertainty; Debt sustainability; Long-run effects; Wirtschaftspolitik; Risiko; Konjunktur; Öffentliche Schulden; Nachhaltigkeit; USA